Research Advance in Manganese Nanoparticles in Cancer Diagnosis and Therapy - Nie, Dengyun; Zhu, Yinxing; Guo, Ting; Yue, Miao; Lin, Mei (Frontiers in Materials, 2022)
As the second reason of causing death after cardiovascular disease for human being, cancer is damaging people all over the world. Fortunately, rapidly developing in the past decade, nanotechnology has become one of the most promising technologies for cancer theranostics. Recent studies have demonstrated that transition metal nanoparticles, especially manganese nanoparticles (Mn-NPs), display great potential for application in various oncology fields due to their unique fundamental properties. Although global scientists have developed a variety of new Mn-NPs and have proved their preponderance in cancer diagnosis and treatment, Mn-NPs are still not approved for clinical use. In this paper, the research progress of Mn-NPs in the fields of cancer diagnosis and therapy in recent years is reviewed. Besides, the future prospect and challenges of Mn-NPs are discussed to explore wider applications of Mn-NPs in clinic. Here, we hope that this review will show a better overall understanding of Mn-NPs and provide guidance for their design in clinical applications for cancer.